2020
DOI: 10.1016/j.mattod.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The controlled large-area synthesis of two dimensional metals

Abstract: The rise of nanotechnology has been propelled by low dimensional metals. Albeit the long perceived importance, synthesis of freestanding metallic nanomembranes, or the so-called 2D metals, however has been restricted to simple metals with a very limited in-plane size (< 10 m). In this work, we developed a low-cost method to synthesize 2D metals through polymer surface buckling enabled exfoliation. The 2D metals so obtained could be as chemically complex as high entropy alloys while possessing in-plane dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 74 publications
0
54
0
Order By: Relevance
“…Michael Faraday study of light and matter interaction onto thin gold leaf showed faint ruby color fluid production was the first ever reported quantum states, too supported its validity [13][14][15][16]. Today quantum physics and computing have certified such quantum things a bit more irony, as formerly noted as unbelievable.…”
Section: Reincarnated Quantum States In 3d Materialsmentioning
confidence: 92%
See 2 more Smart Citations
“…Michael Faraday study of light and matter interaction onto thin gold leaf showed faint ruby color fluid production was the first ever reported quantum states, too supported its validity [13][14][15][16]. Today quantum physics and computing have certified such quantum things a bit more irony, as formerly noted as unbelievable.…”
Section: Reincarnated Quantum States In 3d Materialsmentioning
confidence: 92%
“…2D matrix owes single-layer pattern of crystalline materials owing distinct physical and chemical features leading to assorted applications like photovoltaic, semiconductor, electrode, water-oil separation/purification, marker, bio-sensor, etc. [14]. Amid 2D matrixes self-supporting metallic matrix is very hard to obtain due to involvement of characteristics 3D structural bonding.…”
Section: Specially Reconfigured 2d Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of high‐quality 2D metallic materials is a prerequisite for exploring their properties and potential applications. To date, various synthesis strategies, including wet chemical synthesis, [18b,p,23] epitaxial growth, [18i] mechanical compression/rolling, [18a,24] liquid exfoliation [25] and polymer surface buckling enabled exfoliation, [18j] have been developed for preparation of ultrathin 2D metallic nanosheets. Each synthesis route has its own trait, [1a,26] for example, wet chemical synthesis, including template/space confined‐assisted, [18b,23a] surfactant/ligand‐assisted growth, [23b,c] small molecules/ions‐mediated synthesis, [23d] seeded‐mediated growth, [23b] hydro/solvothermal synthesis [23f,g] and nanoparticle self‐assembly, [17n,27] etc., are most widely applied for fabricating 2D metallic nanosheets in high yield and low cost.…”
Section: Synthesis Of 2d Metallic Materialsmentioning
confidence: 99%
“…However, they were not stable under ambient conditions as the holes in the membranes developed when exposed to air for a few hours. More recently, our group developed a facile, low‐cost method to synthesize large‐scale free‐standing 2D Ti and other multi‐component alloy films (e.g, 2D high entropy alloy and 2D metallic glass) through polymer surface buckling enabled exfoliation (PSBEE) [18j] . As shown in Figure 9a, in a typical synthesis process, the precursory polyvinyl alcohol (PVA) hydrogel substrate was first prepared by 3D printing and after surface smoothing via hot‐pressing, a thin metallic film with desired chemical composition was deposited on PVA surface.…”
Section: Synthesis Of 2d Metallic Materialsmentioning
confidence: 99%